Pengembangan Aplikasi Pemetaan Lahan Berbasis Mobile Menggunakan Geographic Information System (Gis) - Bagus Ardi Pratama; Ledy Elsera Astrianty (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
Geographic Information Systems (GIS) play an important role in the development of mobile-based land mapping applications in Rembang Sub-district. This research aims to assist farmers in filing documents related to farmer data and land geospatial data, supporting more effective and integrated land management. This application is designed to improve the efficiency and accuracy of land mapping and facilitate farmers in managing their farms digitally. The method used in this research is the waterfall method, which involves observations and interviews with farmers as the main users to ensure the application fits the field needs and land conditions. Geospatial data collection is done with GIS technology to reduce data entry errors that often occur in manual methods. Implementation was done with PHP Native & Kotlin programming language, using Visual Studio & Android Studio Code development tools and MySQL for database. Testing was carried out using the User Acceptance Testing (UAT), with the UAT results reaching a satisfaction level of 88.75%. The app enables more effective data management, including geospatial information and relevant farmer data for sustainable farmland monitoring. Research shows that the app improves the efficiency of land mapping and strengthens farmers' capacity to adopt modern technology.